Translation, Validity and Internal Consistency of the Quality of Dying and Death Questionnaire for Brazilian families of patients that died from cancer: a cross-sectional and methodological study - Paiva, Bianca Sakamoto Ribeiro; Valentino, Talita Caroline de Oliveira; Mingardi, Mirella; Oliveira, Marco Antonio de; Franco, Julia Onishi; Salerno, Michelle Couto; Palocci, Helena; Melo, Tais Cruz de; Paiva, Carlos Eduardo (São Paulo Medical Journal, 2023)
BACKGROUND: The Quality of Dying and Death Questionnaire (QoDD) may prove to be an important evaluation tool in the Brazilian context, and, therefore, can contribute to a more precise evaluation of the dying and death process, improving and guiding the end-of-life patient care. OBJECTIVE: To translate and cross-culturally adapt the QoDD into Brazilian Portuguese and measure its validity (convergent and known-groups) and internal consistency DESIGN AND SETTING: A cross-sectional, methodological study was conducted at the Hospital de Câncer de Barretos, Brazil METHODS: A total of 78 family caregivers participated in this study. Semantic, cultural, and conceptual equivalences were evaluated using the content validity index. The construct validity was assessed through convergent validation and known groups analysis [presence of family members at the place of death; feel at peace with dying; and place of death (hospital versus home; hospital versus Palliative Care)]. Internal consistency was evaluated using Cronbach’s alpha. RESULTS: The questionnaire was translated into Brazilian Portuguese and presented evidence of a clear understanding of its content. Cronbach’s alpha values were ≥ 0.70, except for the domains of treatment preference (α = 0.686) and general concerns (α = 0.599). The convergent validity confirmed a part of the previously hypothesized correlations between the Palliative Care Outcome Scale-Brazil (POS-Br) total scores and the QoDD domain scores. The QoDD-Br domains could distinguish the patients who died in palliative care and general wards. CONCLUSION: The QoDD-Br is a culturally adapted valid instrument, and may be used to assess the quality of death of cancer patients.